Modelling and Simulation of Tramway Transportation Systems - A. Capasso; M. Ceraolo; R. Lamedica; G. Lutzemberger; A. Ruvio (Journal of Advanced Transportation)
Electrified guided vehicles typically face routes having a large number of acceleration and braking phases. The braking energy, since the feeding line presents nonreversible electrical feeding substations, can be recovered in the presence of other nearby vehicles. To improve braking energy recovery, one or more storage systems can be positioned along the track. Analysis of effectiveness for the considered solution requires time-domain simulation models, to be created through suitable simulation general-purpose languages or specialised languages/software. In this paper, three different tools for the considered existing tramway were developed, and the main examined characteristics have been compared to each other. Then, analysis of output results was also performed, demonstrating the real cost-effectiveness of introducing one storage device on the considered tramline in operation.